DESIGN, DEVELOPMENT AND EVALUATION OF NOVEL MOUTH DISSOLVING FILM OF TOFACITINIB CITRATE - RAYKAR, MEGHANA; VELRAJ, MALARKODI (International Journal of Applied Pharmaceutics, 2023)
Objective: The aim of the present study was to design and evaluation of mouth dissolving oral films of tofacitinib citrate allowing fast reproducible drug dissolution in oral cavity thus bypassing the first-pass metabolism to enhance the patient convenience and effective treatment for rheumatoid arthritis. Methods: Films have been prepared by way of solvent casting technique by using Hydroxypropyl methylcellulose (HPMC), sodium carboxymethylcellulose, sodium alginate, and gelatin had been used as the hydrophilic film-forming polymeric bases and glycerol as plasticizer. The prepared film evaluated for in vitro disintegration time, tensile strength, content uniformity, folding endurance, swelling index, and in vitro drug release. Results: The results of prepared film pH of all the selected formulation were ranging between 6.1 to 7.5. Thickness of the films was found in the range of 0.07 to 0.19 mm. The folding endurance was found to vary between 95.7 to 105.4-fold, Disintegration time was found 25 to 35, Drug content was found to be for F3 and F6 formulation i.e., 99.035±1.37 and 99.014±0.79. Conclusion: Thus, the current study successfully designed, developed an optimized Tofacitinib citrate formulation.